ACADEMICIAN. DORJGOTOV DECHINGUNGAA, A LEADING SCIENTIST OF THE INSTITUTE OF THE GEOGRAPHY AND GEOECOLOGY OF THE MONGOLIAN ACADEMY OF SCIENCES, WAS AWARDED THE SUPREME DECORATION OF THE MONGOLIAN STATE, THE ORDER OF “CHINGGIS KHAAN” (Mongolian Journal of Geography and Geoecology, 2022)
МОНГОЛ УЛСЫН ШИНЖЛЭХ УХААНЫ АКАДЕМИЙН ГАЗАРЗҮЙ, ГЕОЭКОЛОГИЙН ХҮРЭЭЛЭНГИЙН ЭРДЭМ ШИНЖИЛГЭЭНИЙ ТЭРГҮҮЛЭХ АЖИЛТАН, АКАДЕМИЧ ДЭЧИНГУНГААГИЙН ДОРЖГОТОВ ТӨРИЙН ДЭЭД ШАГНАЛ, ТЭРГҮҮН ЗЭРГИЙН “ЧИНГИС ХААН” ОДОН ХҮРТЛЭЭ.